Transcranial direct current stimulation suggests not improving postural control during adapted tandem position in people with Parkinson’s disease: a pilot study - Legutke, Beatriz Regina [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP]; Orcioli-Silva, Diego [UNESP]; Santos, Paulo Cezar Rocha Dos; Moraca, Gabriel Antonio Gazziero [UNESP]; Vitório, Rodrigo; Beretta, Victor Spiandor [UNESP] (Elsevier, 2023)
Background: Balance impairments in people with Parkinson's disease (PD) demonstrated mainly in challenging postural tasks, such as increased body oscillation may be attributed to the deficits in the brain structures functionality involved in postural control (e.g., motor cortex, midbrain, and brainstem). Although promising results, the effect of transcranial direct current stimulation (tDCS) on postural control in people with PD is unclear, especially in objective measures such as the center of pressure (CoP) parameters. Thus, we analyzed the effects of a single session of tDCS on the CoP parameters during the adapted tandem position in people with PD. Methods: Nineteen people with PD participated in this crossover, randomized, and double-blind study. Anodal tDCS was applied over the primary motor cortex in two conditions of stimulation (2 mA/active and sham) on two different days for 20 minutes immediately before the postural control evaluation. Participants remained standing in an adapted tandem position for the postural control assessment for 30 seconds (three trials). CoP parameters were acquired by a force plate. Results: No significant differences were demonstrated between stimulation conditions (p-value range = 0.15-0.89). Conclusions: Our results suggested that a single session of tDCS with 2 mA does not improve the postural control of people with PD during adapted tandem.
Keywords: Movement disorders; Balance; Brain stimulation; Electrical stimulation; Neurodegenerative disease; Kinetic; Distúrbios do movimento; Equilíbrio (Fisiologia); Estimulação cerebral; Sistema nervoso - Degeneração